Development of Low-Noise Small-Area 24 GHz CMOS Radar Sensor. (9th August 2016) - Yoon, Min; Ryu, Jee-Youl
Abstract : We present a low-noise small-area 24 GHz CMOS radar sensor for automotive collision avoidance. This sensor is based on direct-conversion pulsed-radar architecture. The proposed circuit is implemented using TSMC 0.13  μ m RF (radio frequency) CMOS (f T / f m a x = 120 / 140  GHz) technology, and it is powered by a 1.5 V supply. This circuit uses transmission lines to reduce total chip size instead of real bulky inductors for input and output impedance matching. The layout techniques for RF are used to reduce parasitic capacitance at the band of 24 GHz. The proposed sensor has low cost and low power dissipation since it is realized using CMOS process. The proposed sensor showed the lowest noise figure of 2.9 dB and the highest conversion gain of 40.2 dB as compared to recently reported research results. It also showed small chip size of 0.56 mm 2, low power dissipation of 39.5 mW, and wide operating temperature range of −40 to +125°C.